Thermal and reliability criteria for nuclear fuel safety - Maksymov, Maksym (River Publishers series in chemical, environmental, and energy engineering., 2021)
The book covers basic approaches to the nuclear fuel state of energy reactors in the last stages of the nuclear fuel cycle, these have been developed by the authors based on Ukrainian Nuclear Power Plant (NPP) operational experience. The book is essential reading for anyone concerned with NPP maintenance and safety.